ADVANTAGES OF TEACHING THE LEXICOLOGY DEPARTMENT THROUGH INTERACTIVE MEANS IN NATIVE LANGUAGE LESSONS - Tajiyeva Zuhra Kamalbayevna (Modern American Journals, 2025)
This article presents pedagogical, psychological and practical advantages of teaching the lexicology department of native languages through interactive means. The role of interactive methods in increasing the activity of students, developing independent thinking and vocabulary of speech is analyzed. The study examines the impact of modern digital technologies, electronic resources and game methods on the study of lexical units.
Keywords: Lexicology, interactive methodology, digital tool, learning motivation, modern education, vocabulary.